Distortion Product Otoacoustic Emission Test is Not the Test to Use in Nonclinical Safety Assessment. (May 2022) - Gauvin, David V; McComb, Margaret; Tapp, Rachel; Yoder, Joshua; Zimmermann, Zachary J.
Ototoxicity and ocular toxicity screening are but two examples of specialty product lines that are often employed as Tier II or III nonclinical safety/hazard screening assessments. Compared to the regulatory guidelines that govern over standard toxicology or neurotoxicology programs, there is a paucity of regulatory strategies to address these specialized product lines. With respect to ototoxicity testing, we argue for the inclusion of the "least burdensome principles" adopted by the US FDA in providing the most pragmatic, efficient, and directed identification of potential harm to auditory function in the nonclinical safety arena. We argue for the exclusive use of the auditory brainstem response and the exclusion of the distortion product otoacoustic emissions (DPOAEs) in these Tiered II safety assessment programs. The inclusion of both are a burden on operational staff and, due to the extended episodes of anesthesia required to conduct both assays, this strategy poses a health and welfare concern for the selected animal species to be used. The DPOAE does not provide any sufficiently valid or reliable data above and beyond the gold standard ABR data, followed by complete oto-histopathology and cytocochleogram combination designs.